EQUITY VALUES AND THE EFFECT OF SERVICE GIVEN BY CADRE ON sATISFACTIONâS MEMBER AT BINA KELUARGA BALITA (BKB), POSYANDU, EDUCATION CHILD FOR EARLY AGE (PAUD) HOLISTIC AND INTEGRATED AT KULON PROGO, YOGYAKARTA - Ekoriano, Mario (Widyariset, 2013)
The objective of this study is to measure equity values and identity of services given by cadre and satisfactionâsÂ member at Bina Keluarga Balita (BKB), Posyandu, and Education for Early Age (PAUD) groups holistic integrativeÂ at Kulon Progo, Yogyakarta. This study uses primary data from Evaluation Research of BKB, Posyandu, andÂ PAUD. Samples are groups which have holistic and integrative activities. This research is a qualitative and quantitativeresearch which use General Regression Linier Model with standarized regression [beta coefficient] andÂ can be interpreted as âcorrelationâ. The uses of standarized regression analysis is to test the effect of independentÂ variables on the dependent variable and descriptive interpretatif. The result of this study show that cadre serviceÂ significantly on satisfactionâs member at BKB, Posyandu, and PAUD, Kulon Progo, Yogyakarta.